Using A Numerical Method and A New Mathematical Technique to Analyze Gum Arabic Production Data - Abdel Radi Abdel Rahman Abdel Gadir Abdel Rahman, Sulima Ahmed Mohammed Zubir (Mathematical Statistician and Engineering Applications, 2023)
Our problem is that Gum Arabic needs a certain environmental condition. Factors that influence are difference, Gum Arabic is one of the most important Agricultural exports of North Kordofan State which it used in various industries, its found that Gum Arabic is planning during the rainy season which is joined with temperatures. We aim to analyze Gum Arabic Production Data in North Korodfan State in the period 2011–2017 and to compare with the temperature .We followed the numerical mathematical method using the Newton’s interpolating method and a new mathematical technique using Matlab and we found the following some results : We have the same two polynomials , increasing the production of Gum Arabic in North kordofan State when the temperature increases in addition to the difference in the production of Gum Arabic at the same temperatures is due to other factors that that we leave to the researchers .